Knowledge of Breastfeeding: A descriptive study among mothers in Kirkuk Governorate - Mahmud, nazar (Iraqi National Journal of Nursing Specialties, 2011)
Aims: The present study aims at assessing mothers’ knowledge of breastfeeding in Kirkuk governorate, besides determining the relationship between mothers’ knowledge and some of their demographic attributes. Methodolgy: A descriptive study was used the assessment approach and applied on mothers in Kirkuk governorate from January 15th 2011 to July 25th , 2011. Non-probability sampling a convenience sample of (72) mothers, attending pediatric general hospital in Kirkuk governorate for following up the health status of their children, was selected for the purpose of the study. A questionnaire was developed for the purpose of the study. It was comprised of two parts; the first part includes the mothers’ demographic attributes and the second part assessed the knowledge of breastfeeding with (20) True or False questions. A pilot study was carried out for the period of January 15th to 25th, 2011 to determine the questionnaire reliability through the use of (Test – Retest). A panel of (8) experts was involved in the determination of the questionnaire content validity. Data were analyzed through the application of descriptive statistical data analysis approach (frequency and percentage), and inferential data analysis approach (chi-square). Results: The study findings revealed that more than half (58.3%) of mothers were young, (45.8%) of them had completed primary school, more than two-third (84.7%) of them were housewife mothers, (61.1%) of them have lived inside Kirkuk city, also (61.1) of mothers have more than one children, (63.9%) of them were regularly visited primary health care center during antenatal period and only (40.3%) of them have received antenatal orientation about breastfeeding. According to the level of knowledge of breastfeeding, (66.7%) of mothers answered correctly all questions about breastfeeding, and there was a highly significant relationship between health education during antenatal period and mothers’ knowledge of breastfeeding. Recommendations: The study findings highlight the need for excessive health education about breastfeeding during antenatal period and advice the mothers to comply with recommended visits during pregnancy period.